Gambaran Penderita Diabetes Mellitus tipe 2 dengan Obat Antidiabetik Oral - Grace Y Irene; Kuswinarti Kuswinarti; Maya Kusumawati (Journal of Medicine and Health, 2020)
Uncontrolled hyperglycemia in people with diabetes mellitus can increase the risk of diabetes complications and comorbidities. This study aimed to determine the demographic, clinical, history, complications, and comorbid characteristics of diabetes. The study was conducted with a descriptive method and cross-sectional research design. Data were collected retrospectively using medical record data and using the Finite Population Correction formula with a sample of 115. The results showed the majority of patients were female (67.8%), aged ? 65 years (40.0%), residing in urban (87.6%), high school graduates (35.2%), and unemployed (63.6%). Patients generally have a normal BMI (45.9%) and have several variables that reach the target, namely fasting blood glucose (50.4%), triglycerides (55.3%), and creatinine (69.6%). Patients also had several variables that did not reach the target, namely postprandial 2 hour blood glucose (51.3%), blood pressure (65.8%), total cholesterol (55.6%), HDL cholesterol (54.5%), LDL cholesterol (80.0%), and urea (56.0%). Patients who use oral anti-diabetes generally have used it <5 years (76.3%) and used monotherapy (63.5%). Neuropathy (42.6%) and hypertension (85.9%) were the most common complications and comorbidities of diabetes in this study. Strict glycemic control is an important management for people with diabetes mellitus. Keywords: oral antidiabetic drugs; diabetes mellitus; comorbid